Perupaan Karakter Mang Ohle di Koran Pikiran Rakyat Sebagai Realita Pemikiran Rakyat di Jawa Barat - Agus Triyadi (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2017)
The caricature as part of the drawing works has a straightforward language, verbal, social criticism but is funny and intriguing. The presence of Mang Ohle caricature as a documentation and social criticism characteristic of innocent but smart, such as fictional Sundanese figures are very populist, namely Kabayan, while caricature is critical, satirical, but not make people angry. The Cartoonist Didin Basoeni has a principle,